Pengaruh Abu Cangkang Kemiri Sebagai Substitusi Agregat Halus (Filler) Terhadap Campuran Lapisan AC-WC - Zainal Safariska; Febrina Dian Kurniasari (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
Along with the increasing development, there is also an increasing need for basic materials for road pavement construction, so that it is guided to look for other alternatives using available natural resources, to overcome these problems, research is conducted to find alternative asphalt mix materials with various components of waste, one of which the intended component of waste is candlenut shell waste. This study aims to determine the effect of the substitution of the use of hazelnut shell ash as a substitute for filler on the AC-WC layer concrete asphalt mixture. With the addition of candlenut ash starting from 25%, 50%, and 100%. This study refers to the 2010 Revised 3 Bina Marga Specifications. The results showed that the addition of candlenut ash can improve the value of stability. In general, the characteristic value that meets the requirements of Bina Marga (2014) is found in the composition of 25% of the hazelnut shell filler at asphalt content 6.50%, VIM value 3.70%, VMA 19.49%, flow 3.30 mm and stability namely 1541.70 kg.Keywords: Filler, Candlenut Ash, Mixed Characteristics, Stability